2017
DOI: 10.1111/jvim.14777
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Azithromycin and Compounded Atovaquone for Treatment of Babesia gibsoni in Dogs

Abstract: BackgroundApproximately one‐third of dogs confiscated during dogfighting investigations are infected with Babesia gibsoni. Traditional management of B. gibsoni with polymerase chain reaction (PCR)‐screening, treatment with commercially available azithromycin and atovaquone, and PCR testing after 60 and 90 days is costly and impractical for large numbers of dogs at a time.Hypothesis/ObjectivesTo assess the efficacy of an alternative protocol in which commercial atovaquone was replaced by compounded medication a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Puppies were housed with littermates and nursing dams were housed with litters. Adoptable dogs diagnosed with B. gibsoni were treated with atovaquone (13.4 mg/kg orally q 8 h with a fatty meal) compounded into capsules (Wedgewood Pharmacy) and azithromycin (10 mg/kg orally q 24 h) for 10 days as previously described (Kirk, 2014). Dogs diagnosed with dirofilariasis were treated with a macrocyclic lactone monthly, an oral doxycycline regimen consisting of 1 month on and 2 months off throughout their custody, and with melarsomine following release from legal custody (Kirk, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Puppies were housed with littermates and nursing dams were housed with litters. Adoptable dogs diagnosed with B. gibsoni were treated with atovaquone (13.4 mg/kg orally q 8 h with a fatty meal) compounded into capsules (Wedgewood Pharmacy) and azithromycin (10 mg/kg orally q 24 h) for 10 days as previously described (Kirk, 2014). Dogs diagnosed with dirofilariasis were treated with a macrocyclic lactone monthly, an oral doxycycline regimen consisting of 1 month on and 2 months off throughout their custody, and with melarsomine following release from legal custody (Kirk, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Screening for M128 mutations should primarily be pursued in dogs that remain persistently infected despite treatment. A recent study have shown that that testing <60 days after treatment can yield false positive or false negative results that do not agree with testing performed ≥60 days post‐treatment . Based on these results and the higher proportion of WT cytb detected in follow‐up samples <60 days after the initial positive, PCR testing <60 days from the completion of treatment is not recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Since its emergence in the 1990s, Babesia gibsoni has become the most commonly diagnosed species of Babesia in dogs in the United States of America and is now widely distributed across the country . A&A has been recommended for B. gibsoni, and approximately 80% of treated dogs have clinical “cures” with reductions in parasitemia below the detection limit of sensitive molecular diagnostic assays . Mutations in B. gibsoni cytb genes confer resistance to atovaquone, resulting in treatment failures .…”
Section: Introductionmentioning
confidence: 99%
“…Although no treatment protocol has been shown to consistently resolve B. gibsoni infections in all dogs, current treatment recommendations include multidrug treatment followed by PCR retesting at monthly intervals for up to 120 days after treatment completion . At the time of this study, drug and monitoring costs exceed several hundred dollars per dog; a cost that can put mass treatment of B. gibsoni out of reach in large cases . Dogs that tested positive for B. gibsoni could be monitored during treatment with the iiPCR system.…”
Section: Discussionmentioning
confidence: 99%